Effects of Rules and Feedback on Classroom Behavior of Adolescents in a Residential Treatment Setting. Issue 5 (September 2020) - Chinnappan, Barathi; Rapp, John T.; Burkhart, Barry R.
Over the past 30 years, researchers have shown that various types of group contingency procedures can decrease problem behavior displayed by young children in academic settings. Recently, researchers have demonstrated that presession rules, within-session feedback, and interdependent group contingencies (i.e., contingently delivered tangible and edible items) increased appropriate behavior displayed by detained adolescents in a residential treatment facility. Nevertheless, it is possible that rules with feedback about rule violations could produce comparable outcomes. To address this question, we used a nonconcurrent multiple baseline design across classrooms to evaluate the extent to which rules, visual feedback (i.e., marks on a board denoting rule violations), and postsession feedback decreased problem behaviors in three classrooms within a residential detention facility. Results indicate that problem behavior decreased to less than 10% of observation intervals in each classroom. Results from a social validity measure indicate that the procedures and outcomes were acceptable to the respective classroom teachers.